Mulberry leaves as a feed source for livestock in Kenya: A Review (International Journal of Agricultural Research, Innovation and Technology, 2022)
In Kenya, Mulberry is grown in less than a piece of an acre by most of the farmers. Current acreage of mulberry stands at 250, spread over Western, Nyanza, and Rift Valley and Coastal regions. Mulberry leaves are highly palatable and digestible (70-90%) to ruminants and can be fed to non-ruminants as part of feed ingredient. Protein content and essential amino acid profile in the leaves and young stems varies from 15 to 35% depending on the variety. The Mulberry leaves are highly applicable as supplements replacing concentrates for dairy cattle, as the main feed for goats and sheep, and as an ingredient in rabbits and pigs’ diets. Farmers growing mulberry fodder offer higher protein content to livestock than those relying on different varieties of Napier grass, which have failed to boost milk production despite the amounts fed. In non-ruminant production, fishmeal and soybean meals are the main source of protein. In ruminant production, cottonseed meal and canola meal are the main source of protein. These meals are expensive, inadequate in supply and of variable quality. This often leads to low egg production and poor-quality eggs, hence low income and poverty among farmers. Therefore, efforts have been made to identify locally available protein feed resources that can be used as a protein supplement for livestock. Mulberry leaf meal (MLM) has been identified as a locally available alternative protein and mineral source that are beneficial to livestock and have been proven to improve production.Int. J. Agril. Res. Innov. Tech. 11(2): 1-9, Dec 2021